Stereoselective allylation reactions of acyclic and chiral α-amino-β-hydroxy aldehydes 3: Total synthesis of (+)-1-epi-castanospermine. Issue 28 (12th July 2019) - Myeong, In-Soo; Ham, Won-Hun
Abstract: Stereoselective allylation reactions of acyclic, chiral α-amino-β-hydroxy aldehydes containing four contiguous stereocenters were conducted. Allylation mediated by MgBr2 ∙OEt2 afforded the anti -product. A plausible mechanism of the allylation reaction is also described. The resulting allylation product was used for the total synthesis of (+)-1- epi -castanospermine. Graphical abstract: Image 1